A New Method of the Logical Functions Minimization in the Polynomial Set-Theoretical Format. "Handshaking" Procedure - Rytsar, B.Ye.; Belovolov, А.O. (Control systems & computers, 2021)
A new minimization method of logic functions of n variables in polynomial set-theoretical format has been considered. The method based on the so-called “handshaking” procedure. This procedure reflects the iterative polynomial extension of two conjuncterms of different ranks, the Hamming distance between which can be arbitrary. The advantages of the suggested method are illustrated by the examples.